PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Fahana Febriyanti Anjeli Sarma; Nur Handayani (Jurnal Ekonomi Dan Bisnis, 2025)
This research aimed to analyze the effect of profitability, liquidity, capital structure, and firm size on the firm value of the Automotive companies listed on the Indonesia Stock Exchange (IDX) during 2019-2022. Furthermore, the independent variables were profitability which was a proxy with Return on Asset (ROA), liquidity which was a proxy with Current Ratio (CR), capital structure which was a proxy with Debt Equity Ratio (DER) and firm size which was a proxy with Ln Total Aset. Meanwhile, the dependent variable was firm value which was a proxy with Price to Book Value (PBV). Moreover, the research was quantitative. The data collection technique used purposive sampling. In line with that, 44 samples from 11 automotive companies listed on the Indonesia Stock Exchange during 2019- 2022. Additionally, the data analysis technique used multiple linear regression with the SPSS 26 version. The result and hypothesis test concluded that profitability (ROA) had a positive and significant effect on the firm value. Likewise, liquidity (CR) had a positive and significant effect on the firm value. Similarly, capital structure (DER) had a positive and significant effect on the firm value. However, firm size (Ln Total Aset) had a negative and insignificant effect on the firm value.